2013
DOI: 10.1186/1741-7015-11-98
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ribosomal P protein IgG autoantibodies in patients with systemic lupus erythematosus: diagnostic performance and clinical profile

Abstract: BackgroundThis study was devised to assess the performance of anti-ribosomal P (anti-Rib-P) antibodies in the diagnosis of systemic lupus erythematosus (SLE) and the association of these antibodies with the clinical features of SLE.MethodsWe used a fluorescence enzyme immunoassay to determine anti-Rib-P levels in an SLE group, a rheumatic disease control (RDC) group (rheumatoid arthritis (RA), ankylosing spondylitis, psoriatic arthritis and juvenile idiopathic arthritis), and a healthy control (HC) group. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Nevertheless, other reports have failed to confirm this relationship [12]. A recent meta-analysis suggested that anti-ribosomal-P antibodies are specifically related to psychosis in NPSLE [10].…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, other reports have failed to confirm this relationship [12]. A recent meta-analysis suggested that anti-ribosomal-P antibodies are specifically related to psychosis in NPSLE [10].…”
Section: Reviewmentioning
confidence: 99%
“…Carmona-Fernandes et al . [30] found that the specificity, sensitivity, positive predictive value, and negative predictive value of anti-Rib-P for SLE diagnosis were 99.4%, 14.2%, 90%, and 76.4%, respectively. Although, anti-Rib-P was not clearly associated with any clinical condition, including NPSLE, in that study, nonetheless, the effects of these autoantibodies on the CNS have been addressed in several other studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that antiphospholipid antibodies including anti-cardiolipin and lupus anti-coagulant are some of the strongest NPSLE-related factors expressed especially in relation to cerebrovascular disease [4,5]. One study also reported anti-ribosomal P antibodies as risk factors for SLE psychosis [6]; however, this is inconclusive since another report showed no relation between these antibodies and neuropsychiatric illness [7]. Moreover, anti-double stranded DNA antibodies (anti-dsDNA), which are the most represented autoantibodies in SLE, are reported to cross-react with NR2A and NR2B subunits of the N-methyl-d-aspartate receptor (NMDAR) [8,9].…”
Section: Cns Involvement In Slementioning
confidence: 78%